From Open Content to Open Course Models: Increasing Access and Enabling Global Participation in Higher Education - Morgan, Tannis; Carey, Stephen (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2009)
Two of the major challenges to international students’ right of access to higher education are geographical/economic isolation and academic literacy in English (Carey, 1999, Hamel, 2007). The authors propose that adopting open course models in traditional universities, through blended or online delivery, can offer benefits to the institutions and to the open education movement itself, in particular with non-Anglophone students. This paper describes the model and an implementation with undergraduate students in Canada, Mexico, and Russia. The implementation of the model was examined in three studies, which relied on data collected from student interviews, instructor observations and reflections, instructor interviews, course documents, and discussion forum transcripts. The authors note that the main benefit of an open course model is the development of academic literacy for students of English as an Other Language (EOL). Other benefits include 1) international course transfers, 2) breadth of professorial exposure for the students, 3) flexibility in professors’ employment and professional development, and 4) course credits for students. Some of the challenges include 1) varying levels of Internet access, 2) coordination of the participation of the instructors, and 3) different teaching and learning practices. The authors conclude that an open course model might be applied in various contexts, such as in disciplines where global perspectives are important, in applied/professional programs, and in distance or face-to-face courses. Also, the model is useful for students working together on research, case studies, or joint projects, and it could be applied within an institution to enhance inter-disciplinary content and approaches.